Wearable mixed-reality holographic guidance for catheter-based basal ganglia hemorrhage treatment - Ye Li; Wenyao Zhang; Ning Wang (Interdisciplinary Neurosurgery, 2023)
Background: Bedside freehand catheter insertion for the treatment of basal ganglia hemorrhage currently remains the major method due to its simplicity and efficiency, but it is associated with low precision. We retrospectively evaluated the feasibility and accuracy of using a wearable mixed-reality holographic computer to guide catheter-based basal ganglia hemorrhage treatment compared to the freehand method. Methods: We collected 30 patients who initially underwent either mixed-reality holographic guided catheter insertion (holographic guidance group) or freehand catheter insertion (freehand group). Data of pre- and postoperative CT images in both groups and surgical plans of the holographic guidance group were retrieved from the database. The additional time for holographic guidance was quantified. For both groups, we calculated the number of cases in which the catheter tip was initially outside the hematoma and the number of times for catheter repositioning. Catheter insertion accuracy was quantitatively evaluated using the target deviation. Results: The average additional time required for holographic guidance was 36.65 ± 15.18 min. In the holographic guidance group, all the cases had catheter tips initially inside the hematoma, and none of them needed catheter repositioning. In the freehand group, 3 cases had their catheter tips initially outside the hematoma, and 5 catheter repositioning procedures were performed. The mean target deviation was 5.46 ± 2.22 mm in the holographic guidance group and 12.57 ± 6.77 mm in the freehand group (p < 0.001). Conclusions: We preliminarily demonstrated the feasibility and accuracy of wearable mixed-reality holographic guidance for the treatment of basal ganglia hemorrhage.